Elwood R. Quesada papers - Quesada, Elwood R. (Elwood Richard), 1904-
Correspondence, memoranda, speeches, reports, personnel file, charts, drawings, and other papers documenting Quesada's career as a U.S. Air Force officer and as director of the Federal Aviation Administration. Subjects include his service as commanding general of the IX Fighter Command and the IX Tactical Air Command in North Africa and in Europe during World War II, unification of the armed forces, the B-36 bomber investigation, Quesada's command of the U.S. Joint Chiefs of Staff Joint Task Force-3 engaged in conducting a series of atomic tests on the Pacific atoll of Eniwetok, and work of the Air Force Board of Review for Tactical Operations.
Air Force officer and public official. Died 1993.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Air Force. -- IX Fighter Command; United States. -- Air Force. -- IX Tactical Air Command; United States. -- Air Force. -- Board of Review for Tactical Operations; United States. -- Federal Aviation Administration; United States. -- Joint Chiefs of Staff. -- Joint Task Force-3.; B-36 bomber; Nuclear weapons -- Testing; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Africa, North; World War, 1939-1945 -- Europe; Eniwetok Proving Grounds (Marshall Islands); United States -- Armed Forces; Air Force officers; Public officials